2008
DOI: 10.1021/jf802254p
|View full text |Cite
|
Sign up to set email alerts
|

Moisture and Temperature Triggered Release of a Volatile Active Agent from Soy Protein Coated Paper: Effect of Glass Transition Phenomena on Carvacrol Diffusion Coefficient

Abstract: Carvacrol release from SPI-coated papers was evaluated at different relative humidities (RH; 60, 80, and 100%) and storage temperatures (5, 20, and 30 degrees C). Effective carvacrol diffusivities were determined from experimental release kinetics and by using a mathematical model based on Fick's second law. Increasing storage temperature and RH lead to an increase of carvacrol diffusivity. Depending on the relative humidity, the carvacrol effective diffusivity varied from 1.71 x 10(-16) to 138 x 10(-16) m(2)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 30 publications
3
37
1
Order By: Relevance
“…The carvacrol diffusion within the paper was assumed to be non-rate limiting. Indeed, the diffusivity of carvacrol in the paper (5.9 10 À14 m 2 s À1 ; Chalier et al, 2009) was 15 times higher than that observed in the gluten layer at 30 C and 60% RH (0.38e0.71 10 À14 m 2 s À1 ). Even if some carvacrol were to diffuse into the paper layer, the equilibrium would be reached very quickly (the diffusion from paper toward atmosphere being impossible due to the contact with the support) and would not disturb carvacrol diffusion occurring in the protein layer ( Fig.…”
Section: Mathematical Modelmentioning
confidence: 72%
See 2 more Smart Citations
“…The carvacrol diffusion within the paper was assumed to be non-rate limiting. Indeed, the diffusivity of carvacrol in the paper (5.9 10 À14 m 2 s À1 ; Chalier et al, 2009) was 15 times higher than that observed in the gluten layer at 30 C and 60% RH (0.38e0.71 10 À14 m 2 s À1 ). Even if some carvacrol were to diffuse into the paper layer, the equilibrium would be reached very quickly (the diffusion from paper toward atmosphere being impossible due to the contact with the support) and would not disturb carvacrol diffusion occurring in the protein layer ( Fig.…”
Section: Mathematical Modelmentioning
confidence: 72%
“…The mathematical model previously presented by Chalier et al (2009) was used to model the anti-microbial agent release from the coated paper toward atmosphere. This model was successfully applied by these authors on soy protein isolate coated paper and was thus used in this study, the main assumptions being the same:…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…When applied as coatings, more results deal with plastic coatings than with paper and board coatings. In consequence to this, the application on paper has been studied only for a few proteins such as whey proteins [8,9,32,33], isolated soy proteins [214,[278][279][280][281][282], caseinates [1,7,115,121], wheat gluten [32,280,[283][284][285] and corn zein [1,37,234,235]. As could be observed so far, the literature is countless and it is of course also expected that some of the results on standalone films and on coatings on different substrates can be transferred to paper at least as trends.…”
Section: Application To Cellulose Based Productsmentioning
confidence: 99%
“…In this regard, the release rate of the active agents from the packaging material is critical in order to maintain the content of a given preservative above the minimum inhibitory concentration during the desired food shelf life (Chalier et al, 2009).…”
Section: Active Packaging Materials Release Kineticsmentioning
confidence: 99%